Wärmeaustausch an Nicht-Newtonschen Flüssigkeiten in Apparaten mit rotierenden Elementen - Y. Trouilhet; F. Widmer (CHIMIA)
A model for the flow and heat exchange in different rotative apparatus in chemical engineering is presented. The heat of dissipation, the non-Newtonian behaviour and the temperature dependance of the viscosity are taken in account in this model. The rotor power, heat flux at the walls and temperature profiles in the liquid are determined as function of the rotor speed, wall temperatures, physical constants of the liquid and gap geometry.